2015
DOI: 10.1021/acs.est.5b00734
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Area of Protection “Natural Resources” in Life Cycle Assessment

Abstract: Life cycle impact assessment (LCIA) in classical life cycle assessment (LCA) aims at analyzing potential impacts of products and services typically on three so-called areas of protection (AoPs): Natural Environment, Human Health, and Natural Resources. This paper proposes an elaboration of the AoP Natural Resources. It starts with analyzing different perspectives on Natural Resources as they are somehow sandwiched in between the Natural Environment (their cradle) and the human-industrial environment (their app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 18 publications
0
81
0
Order By: Relevance
“…This new debate can be illustrated by the recently published work from Dewulf, et al [70] who proposes to divide the AoP "Natural Resource" into five safeguard subjects including environmental, economic and social aspects, and the presentations of the 55th Discussion Forum on LCA in Zürich, during which the definition of the AoP "Natural Resource" was addressed as a key question [65]. Indeed, there is no agreement in the scientific community on the nature of the impact caused by resource consumption: while the AoP "Natural Resources" has been defined in the framework of environmental LCA and thus assumes that natural resource consumption is an environmental issue, the idea that resource consumption also considers other (provisioning) capacity of resources to fulfil humans needs is emerging [70]. The unclear definition of this AoP can partly explain the wide range of approaches followed by LCIA methods concerning the evaluation of resource consumption and the lack of consensus around which method to use.…”
Section: Entities Impacted By Resource Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This new debate can be illustrated by the recently published work from Dewulf, et al [70] who proposes to divide the AoP "Natural Resource" into five safeguard subjects including environmental, economic and social aspects, and the presentations of the 55th Discussion Forum on LCA in Zürich, during which the definition of the AoP "Natural Resource" was addressed as a key question [65]. Indeed, there is no agreement in the scientific community on the nature of the impact caused by resource consumption: while the AoP "Natural Resources" has been defined in the framework of environmental LCA and thus assumes that natural resource consumption is an environmental issue, the idea that resource consumption also considers other (provisioning) capacity of resources to fulfil humans needs is emerging [70]. The unclear definition of this AoP can partly explain the wide range of approaches followed by LCIA methods concerning the evaluation of resource consumption and the lack of consensus around which method to use.…”
Section: Entities Impacted By Resource Consumptionmentioning
confidence: 99%
“…Therefore, LCIA methods aim to evaluate the impact of life cycle inventories on these entities. The three main AoPs in LCA are "Human Health", "Ecosystem Quality" and "Natural Resources" [70]. Several LCA methods consider the impact of resources on an AoP other than "Natural …”
Section: Entities Impacted By Resource Consumptionmentioning
confidence: 99%
“…The interest in AoPs can go beyond the purely ecological sector [77]. Societal and social welfare or the fundamental adherence to the precautionary principle is also mentioned in this context [75,78]. Both the definition and the logical connection between AoPs contain normative stipulations that stem from anthropocentric, pathocentric, and biocentric positions [79].…”
Section: Areas Of Protectionmentioning
confidence: 99%
“…Some authors argue that the man-made-anthropogenic-environment should also be addressed as an independent AoP that inherently goes beyond the ecological sphere [81]. In that sense, Dewulf proposes five different perspectives of natural resources, which comprise not only the natural resources' asset, their provisioning capacity, and their role as constituents in global ecosystem functions but also their provisioning function for human welfare and human welfare as an inclusive category itself [78].…”
Section: Areas Of Protectionmentioning
confidence: 99%
“…Steen (1999) was the first to propose surplus cost as an indicator to assess the life cycle impacts of products, services and technologies. Despite this development from the 90s and others that followed, currently there is still extensive debate about natural resources in life cycle impact assessment (LCIA) (Dewulf et al 2015;Drielsma et al 2016;Lieberei and Gheewala 2017;Sonderegger et al 2017;Steen and Palander 2016). The European Commission-Joint Research Centre-Institute for Environment and Sustainability (2011) indicated surplus costs as a promising approach to quantify abiotic resource scarcity but has, nevertheless, considered it not mature for recommendation in the evaluation of product life cycle impacts.…”
Section: Responsible Editor: Gian Luca Baldomentioning
confidence: 99%